Students’ theses as tool for prospecting major courses in biology study program - Janra, Muhammad; Herwina, Henny (Journal on Biology and Instruction, 2025)
Students in the Department of Biology at Andalas University are required to write a thesis based on one of ten core subjects: animal systematics, plant systematics, animal ecology, plant ecology, microbiology, genetics, animal physiology, plant physiology, animal structure and development, and plant structure and development. This study analyzed the dynamics of student interest in these subjects as thesis topics from 2000 to 2019. A total of 1,201 thesis titles were analyzed descriptively based on the average and frequency per year, and visualized in tables and graphs. The results showed that microbiology was the most popular (14.7 theses/year), followed by plant physiology (9.8) and animal systematics (9.4). The two least popular fields were animal and plant structure and development (fewer than two theses/year). Unstructured interviews with final-year students revealed that the availability of supervisors, research funding, and laboratory access were the primary factors influencing topic selection. Theses with a single topic were more numerous than those with mixed topics. Integrating two or more courses into one thesis can be a solution to increase interest in less popular courses. If this approach is not effective, it may be worth considering removing the course from the elective list for the final project. The implications of these findings suggest that enhancing interdisciplinary research opportunities might also encourage broader topic selection. Continuous evaluation of the curriculum is necessary to ensure that elective subjects remain relevant and aligned with students’ interests and departmental capabilities, potentially leading to curriculum refinement or restructuring.